Management of downy mildew (Pseudoperonospora cubensis (Berk. & Curt.) Rostov.) of cucumber under protected cultivation - Reshma Raj T (Department of Plant Pathology, College of Horticulture, 2016)
The present study entitled “Management of downy mildew (Pseudoperonospora cubensis (Berk. & Curt.) Rostov.) of cucumber under protected cultivation” was conducted in the Department of Plant Pathology, College of Horticulture, Vellanikkara during the period from October to April 2015-16. The major objective was to assess the incidence and severity of downy mildew of cucumber under protected cultivation and to formulate eco-friendly management package against the disease. A survey was conducted in Thrissur district during January to December 2015 in nine polyhouses. During the survey, incidence of downy mildew was noticed in all the polyhouses where cucumber was cultivated irrespective of the season and the disease severity varied from 11.33 to 35.75per cent. There is a significant positive correlation between the disease incidence and severity with relative humidity (RH) inside the polyhouse and negative correlation with temperature. Morphological characterization of the pathogen present on the diseased leaves collected during survey revealed that sporangiophores are dichotomously-branched at acute angles that tapered to curved pointed tips. Large lemon shaped, brownish yellow sporangia are borne singly at the tip of the sporangiophore. Field experiments were conducted simultaneously inside the polyhouse and rain shelter for management of downy mildew with 12 treatments and three replications. The treatments included two biocontrol agents (Trichoderma viride and Pseudomonas fluorescens), cowdung supernatant, two biofungicides (garlic and calphomil) and two systemic (potassium phosphonate + hexaconazole and cymoxanil + mancozeb) and one contact (mancozeb) fungicide. Soil solarisation inside the protected structures was included as part of treatments viz., T1 (soil solarisation + seed treatment and soil application + foliar spray with T. viride) and T2 (soil solarisation + seed treatment and soil application + foliar spray with P. fluorescens). It was found that soil temperature at 10 cm depth was higher in solarized soil when compared to nonsolarised soil by 4 oC and 3.5 oC inside polyhouse and rain shelter respectively. It was also recorded that the population of soil microflora was reduced due to solarisation in protected structures. Among the treatments, T10 (foliar spray with cymoxanil + mancozeb- 0.2%) was the most effective for management of downy mildew in both polyhouse and rain shelter followed by T11 (foliar spray with mancozeb-0.2%) and T1 (soil solarisation + seed treatment and soil application + foliar spray with T. viride) and these were statistically on par. Moreover, highest yield was recorded in T1 followed by T2 (soil solarisation + seed treatment and soil application + foliar spray with P. fluorescens). Correlation analysis was performed with the meteorological data and per cent disease severity (PDS) at periodic intervals and it was confirmed that there is significant positive correlation between PDS and RH and negative correlation between PDS and temperature inside the structure. Economic analysis of the field experiments suggested that the treatments with biocontrol agents recorded the highest B:C ratio. Analysis of population of phyllolane microflora proved that there was drastic reduction in the population of phylloplane fungi and bacteria after spraying with chemical fungicides whereas the population increased after spraying with biocontrol agents. Survival of biocontrol agents on the phylloplane of cucumber was also studied and it was found that both T. viride and P. fluorescens, survived on the leaf surface upto 15 days after foliar application. Results of the survey and field experiments indicated that, there is a chance of incidence of downy mildew inside the structure if the RH is ≥ 79 per cent. Downy mildew of cucumber inside the protected structures could be effectively managed by biocontrol agents, which gave a reduction in disease severity comparable to that of systemic fungicide. Powered by TCPDF (www.tcpdf.org)